1980
DOI: 10.1007/bf00688529
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement treatment for Tay-Sachs disease brain cells in culture utilizing Concanavalin A-mediated hexosaminidase A uptake: Biochemical and morphological evidence of GM2 mobilization

Abstract: When Concanavalin A (Con A) is bound to the cell membrane, it functions as an artificial enzyme receptor, mediating the binding and intracellular incorporation of significant amounts of exogenous hexosaminidase A (Hex A) into Tay-Sachs disease (TSD) glia cells. The treated cells retained almost 50% of incorporated Hex A activity after 3 days incubation in Hex A free medium. Hex A was released from Con A within the cell and was available as free enzyme. Biochemical analysis of gangliosides in Con A and Hex A tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It has been demonstrated in rats that active HEX A can be delivered to the cerebrum after osmotic disruption of the BBB, and that the enzyme is taken up by subcellular organelles presumed to be lysosomes (30,31). Uptake of HEX by brain cells may be a receptor-mediated event, which suggests that the process could be facilitated if the enzyme is recognized by the receptor (32)(33)(34). The potential for amelioration of stored substrate in the CNS is supported by studies that have shown degradation of accumulated substrate in systemic organs after intravenous enzyme infusion in another feline model of GM2-gangliosidosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in rats that active HEX A can be delivered to the cerebrum after osmotic disruption of the BBB, and that the enzyme is taken up by subcellular organelles presumed to be lysosomes (30,31). Uptake of HEX by brain cells may be a receptor-mediated event, which suggests that the process could be facilitated if the enzyme is recognized by the receptor (32)(33)(34). The potential for amelioration of stored substrate in the CNS is supported by studies that have shown degradation of accumulated substrate in systemic organs after intravenous enzyme infusion in another feline model of GM2-gangliosidosis (24).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent reports describe the use of lectins as artificial receptors bound t o the cell membrane which facilitate the entry of enzymes into cells. Gonzalez-Noriega and Sly [4] studied the use of concanavalin A to assist uptake of glycoproteins into fibroblasts; Juliano et a1 [9, 101 used concanavalin A to introduce placental hexosaminidase B into Sandhoff disease fibroblasts and Brooks et a1 [2] studied concanavalin A-assisted uptake of placental hexosaminidase A by TSD-cultured cerebellar cells. Therefore, concanavalin A is a useful agent for introducing low uptake forms of glycoprotein enzymes into enzyme-deficient cells.…”
Section: Enzymes Into Cells Cohen Et A1 [3] Used Immunoglobulin-coatmentioning
confidence: 99%
“…Electron microscopic studies of the cultured cells were performed as described previously . The methodology for the tissue culture lipid studies and the quantitative analytic studies of the Con A mediated Hex A uptake were reported by Brooks et al (1980Brooks et al ( , 1981. cells over a 10-day period after labelling with a D-[14C3glucosamine show a turnover in all ganglioside fractions, except GMz.…”
mentioning
confidence: 97%